Calcular:
1 .Sendo P(X) = x2+ 2x e Q(X) = 2x2+ x
a) P(X) + Q(X)
2. Sendo P(X) = 2x2+ x e Q(X) = x2
b) P(X) + Q(X)
3. Sendo P(X) = 2x3+ x2+ 3x e Q(X) = x3+ 2x2+ 5x
c) P(X) + Q(X)
4 .Sendo P(X) = 2x4- 3x3+ 2x2+ 6x + 1 e Q(X) = 3x4+ 2x3+ x2+ 4x + 1
d) P(X) + Q(X)
5. Sendo P(X) = 2x5+ 1 e Q(X) = x5
e) P(X) - Q(X)
6. Sendo P(X) = 3x4+ 2x3+ x2- 4x e Q(X) = x3+ 2x2+ 5x
f) P(X) + Q(X)
7. Sendo P(X) = 2x6+ 1 e Q(X) = x6+ 2
g) P(X) - Q(X)
8. Sendo P(X) = 3x8+ 5x7+ 8x e Q(X) = x8+ 2x7- 5x
h) P(X) + Q(X)
Soluções para a tarefa
Respondido por
1
Resposta:
1 .Sendo P(X) = x2+ 2x e Q(X) = 2xx2334
Perguntas interessantes
Biologia,
9 meses atrás
Física,
9 meses atrás
Artes,
11 meses atrás
Matemática,
11 meses atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás